Correlation of Calcium, Phosphorus, Uric Acid and Magnesium Level in Serum and 24 hours Urine of Patients with Urolithiasis - Gyawali, P R; Joshi, B R; Gurung, C K (Kathmandu University Medical Journal, 2012)
Background Urinary stones disease is common pathology encountered in urological practice in Nepal. Supersaturated urine and its stagnation are well known facts for the development of urolithiasis. Metabolic disorders like hypercalciuria, hyperuricaemia, hypocitraturia are also responsible for formation of urolithiasis. Objective The aim of this study was to identify the level of calcium, phosphorus, uric acid, and magnesium in the blood and urine of Nepalese patients with urinary stones. Methods This study was conducted over a period of six months (From May to November 2010). It is a descriptive cross sectional study and quantitative method was used for analysis. Primary data were collected and utilized from 79 cases. Results: The prevalence of urolithiasis in male patients was 65.8% and 34.2% in female patients (p<0.05). Serum calcium in stone former and non-stone former was 8.3±1.2 and 7.5±1.5 (p<0.01) respectively. Serum phosphorus and uric acid in both groups were statistically not significant (p value 0.269 and 0.597 respectively) though in 24 hours urine of stone formers value of phosphorus was 447.9±182.4 but in non-stone formers it was 186.5±118.7 (p<0.001). Magnesium level in urine was 48.1±69.7 and 131.4±86.9 (p<0.001) respectively. Conclusion Higher level of calcium in serum was found in patients with urolithiasis in our population. Though phosphate level in blood serum was not different in the both groups but in urine phosphate and magnesium levels were significantly different. DOI: http://dx.doi.org/10.3126/kumj.v9i2.6289 Kathmandu Univ Med J 2011;9(2):54-6